(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2018)
In this work we investigate the use of MasteringPhysics in teaching an introductory physics course at United Arab Emirates University. The subject of the course is classical mechanics offered for science students. Online homework assignments are managed to assess the course learning outcomes. During the assignment 92 students see their grades and have the choice to receive computer feedback on each outcome, and they have the chance to correct their answers until the assignment is completed. The final score is based on the number of trails and hints they obtained by the computer. The main objective from this method is to improve students’ learning. Therefore, the average grade for all homework assignments for each student was calculated, and correlated to the students’ achievements in the final exam. A relatively good correlation was observed, and most of the course outcomes are achieved.